The prevalence of visual impairment among adults with disabilities / Muhamad Ali Imran Muhamad Yusni - Muhamad Yusni, Muhamad Ali Imran (2016)
Purpose: The purpose of this retrospective study was to determine the prevalence of visual impairment among adults with disabilities. The correlation of visual impairment with demographic data, visual acuity and refractive error were also investigated. Materials & Methods: The clinical eye examination data in community rehabilitation center around Selangor from year 2012 until 2014 were reviewed. Data of adults with disability were included. Results: Thirty five eye examination data of adults with disability were reviewed. The prevalence of VI among adults with disabilities was 17.14%. Learning disability had the highest prevalence of VI (11.43%), followed by physical disability (2.86%) and multiple disabilities (2.86%). There were poor correlation of VI between types of disability (r=-0.25, p>0.05), gender (r=-0.39, p>0.05) and age (r=+0.023, p>0.05). Surprisingly, a weak correlation was revealed in VI with visual acuity (r=-0.09,p<0.05). Refractive error also showed a weak correlation and no significant between visual impairment and refractive error (r=-0.083, p>0.05). Conclusions: These finding showed a significant burden of vision impairment among adults with disability. The poor and insignificant correlation of VI with some factors might be due to incomplete and insufficient of clinical eye examination data. However, the important of eye examination and early detection of vision problem still need to be highlighted among individual with disability in primary eye care services.